2008
DOI: 10.4049/jimmunol.180.11.7240
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-κB1 by OX40 Contributes to Antigen-Driven T Cell Expansion and Survival

Abstract: The costimulatory molecule OX40 (CD134) is strongly required in many instances for effective T cell‐mediated immunity, controlling proliferation and survival of T cells after encountering specific antigen. We previously found that the functional targets of OX40 are survivin and aurora B that regulate proliferation, and Bcl‐2 anti‐apoptotic family members that regulate survival. However, the intracellular pathways from OX40 that mediate these effects are unclear. Here, we show that OX40 signaling can target the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 57 publications
(57 reference statements)
6
115
1
Order By: Relevance
“…One of them, CD27, has been previously linked to Eomes expression (21). However, we observed that neither activation of CD27 nor OX40 signaling with agonist antibodies (22,23) altered Eomes expression in memory T cells (Fig. S1B).…”
Section: Significancecontrasting
confidence: 39%
See 2 more Smart Citations
“…One of them, CD27, has been previously linked to Eomes expression (21). However, we observed that neither activation of CD27 nor OX40 signaling with agonist antibodies (22,23) altered Eomes expression in memory T cells (Fig. S1B).…”
Section: Significancecontrasting
confidence: 39%
“…To address this question, we altered NFκB signaling using gain and loss-offunction approaches in proliferating T cells. First, we transduced CD8 T cells with a construct that encodes constitutive active IKKβ (CA-IKKβ) to enhance NFκB signaling (22). CA-IKKβ GFP + -transduced cells exhibited lower levels of IκBα (as a consequence of increased proteosomal degradation) than their EV-transduced counterparts, confirming constitutive NFκB signaling (33).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, effective ΙΚΚβ expression alone is sufficient to restore the defective proliferation and survival of OX40-deficient T cells in vivo when responding to antigen. Thus, OX40 signals regulate T cell number and viability through the NF-κΒ1 pathway that controls the expression and activity of intracellular targets for proliferation and survival (32). Collectively, mediated by PI3K/PKB/NF-κB pathways, CD28 and OX40 regulate expression of bcl-2 family members and survivin/ aurora B that control T cell proliferation, cell cycle progression, and longevity (16,33).…”
Section: Common Pi3k/pkb/nf-κβ Pathwaysmentioning
confidence: 99%
“…OX40 is a costimulatory molecule constitutively expressed by Treg cells and expressed upon activation by T effector (Teff) cells. Triggering of OX40 has opposite effects on these two T-cell populations: Treg cells are inhibited in their suppressive functions [3][4][5][6], while Teff cells are stimulated to proliferate, survive and gain memory phenotype [7][8][9][10][11]. Treatment of different types of mouse transplantable tumors with the mAb OX86, the agonist of OX40, favors tumor rejection thanks to its double effect on Treg and Teff cells [3,12].…”
Section: Introductionmentioning
confidence: 99%